PERBANDINGAN VEGETASI GULMA PADA PERKEBUNAN KELAPA SAWIT (Elaeis guineensis Jacq.) MENGHASILKAN DAN BELUM MENGHASILKAN DI LAHAN GAMBUT - Endah Dwi Susanti; Novita Hera; Syukria Ikhsan Zam (Jurnal Agroteknologi, 2021)
Weed vegetation analysis is important to do in order to know the composition and structure of the vegetation to determine the appropriate weed control measures. This study aims to compare the composition and structure of weeds on peatland immature oil palm plantations and mature palm. This research was conducted from October to December 2020. Vegetation analysis was carried out using a survei method with purposive sampling technique. The parameters observed were density, frequency, dominance, important value index (INP), summed dominance ratio (SDR) and species diversity index (H'). The results showed that the composition of weeds on immature oil palm plantations was found 12 species with number of individual 847, while on mature palm found 9 species with number of individuals 980. The dominant weed structure on immature oil palm plantations is Lempuyangan with SDR values 29,9 % and mature palm is Bandotan with SDR value 23,4%. Weed diversity index on immature oil palm plantations and mature palm is categorized as high with a value of 1.50 for immature oil palm plantations and 1.65 for mature palm.